2021
DOI: 10.1186/s12879-021-05773-w
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine in the treatment of outpatients with mildly symptomatic COVID-19: a multi-center observational study

Abstract: Background Hydroxychloroquine has not been associated with improved survival among hospitalized COVID-19 patients in the majority of observational studies and similarly was not identified as an effective prophylaxis following exposure in a prospective randomized trial. We aimed to explore the role of hydroxychloroquine therapy in mildly symptomatic patients diagnosed in the outpatient setting. Methods We examined the association between outpatient … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…The use of hydroxychloroquine for the treatment of COVID-19 is controversial. Some studies have reported that this drug reduces mortality [18], but others have not confirmed this finding [19]. Our subjective clinical impression is that hydroxychloroquine can be useful in the first days of hospitalization.…”
Section: Plos Onementioning
confidence: 90%
See 1 more Smart Citation
“…The use of hydroxychloroquine for the treatment of COVID-19 is controversial. Some studies have reported that this drug reduces mortality [18], but others have not confirmed this finding [19]. Our subjective clinical impression is that hydroxychloroquine can be useful in the first days of hospitalization.…”
Section: Plos Onementioning
confidence: 90%
“…Coronavirus disease-19 (COVID- 19), produced by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become a global pandemic, giving rise to a serious health threat globally. Several countries have seen a two-wave pattern of reported cases, with a first wave in spring and a second in late summer and autumn [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…These reviews conclude that there is currently insufficient evidence for the use of CQ/HCQ as effective COVID-19 treatments. To date (February 2021), the debate about the efficacy of HQC in the treatment of COVID-19 patients is continuing with many conflicting reports [ 50 , 51 ]. As additional randomised controlled trials have been recommended [ 1 ], we urge that G6PD deficiency-related effects be considered in African participants in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of benefits could be due to the inability of HCQ to kill the SARS-CoV-2 virus beyond in vitro settings or could be due to the timing of using the medicine late in the disease progression pathway. The latter explanation is based on the possible benefits of HCQ in mildly symptomatic [36] or asymptomatic patients in whom perhaps the suggested mechanism of reducing viral load (and reducing transmission) is not onerous.…”
Section: Discussionmentioning
confidence: 99%